Inovasi Model Pembelajaran Bahasa Indonesia di Sekolah Dasar - Ghufron, Syamsul (Jurnal Pendidikan dan Pengajaran, 2024)
The background of this study is the need for an innovative learning model to improve the quality of Indonesian Language learning at the elementary level. This study aims to analyze the innovation of the Indonesian Language learning model (IMPBI) in elementary schools. This study is classified as a systematic literature review with a focus on the topic of IMPBI in elementary schools. Data sources are taken from Google Scholar in the form of relevant articles or research reports. Data collection was carried out using the keywords "innovative learning models in elementary schools" and "IMPBI in elementary schools", resulting in 20 articles. The data analysis method used is descriptive analysis of the existing findings. The results of the study indicate that innovative Indonesian Language learning models include the SAVI, PAIKEM, CTL, and others. The innovative learning methods found include the role play method, SQ3R, SQ4R, PQ4R, and others. The conclusion of this study emphasizes the importance of implementing innovative learning models and methods to improve the effectiveness of Indonesian Language learning in elementary schools. The implication is the need for adaptation and implementation of various innovative learning models in elementary education environments.